1996
DOI: 10.1007/s004240050202
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-dependent modulation of smooth muscle intracellular calcium and force by altered intracellular pH

Abstract: Measurements of simultaneous force and intracellular Ca2+ concentration ([Ca2+]i) in rat uterine smooth muscle have been made to elucidate the mechanisms involved when force produced spontaneously, by high-K+ depolarization or carbachol is altered by a change of intracellular pH (pHi). Rises in force and [Ca2+]i were closely correlated for all forms of contraction, with the Ca2+ transient peaking before force. In spontaneously active preparations, alkalinization significantly increased, and acidification decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…Intracellular acidification, at constant pHo, abolished spontaneous contractions in all tissues tested. These effects was similar to those reported in rats and women (Taggart and Wray, 1993, Parratt et al, 1994, 1995a (Taggart et al, 1996). Thus, acidification reduced [Ca2+].…”
Section: Resting Ph and Contractile Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…Intracellular acidification, at constant pHo, abolished spontaneous contractions in all tissues tested. These effects was similar to those reported in rats and women (Taggart and Wray, 1993, Parratt et al, 1994, 1995a (Taggart et al, 1996). Thus, acidification reduced [Ca2+].…”
Section: Resting Ph and Contractile Activitysupporting
confidence: 89%
“…modulate force in a variety of smooth muscles (Wray, 1988;Austin and Wray, 1994;Burdyga et al, 1996). In myometrial smooth muscle obtained from both rats (Taggart and Wray, 1993) and women (Parratt et al, 1994(Parratt et al, , 1995a, intracellular acidification decreases, and intracellular alkalinization increases, spontaneous force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular pH has been shown to be a potent modulator of uterine force, with intracellular acidification reducing or even abolishing contractions (Taggart & Wray, 1993;Parratt et al 1994). We have previously found that when intracellular pH is lowered, Ca 2+ transients are suppressed and intracellular Ca 2 falls (Taggart et al 1996). Measurement of membrane potential showed action potentials were also abolished by acidification (Taggart et al 1996).…”
Section: Contractionmentioning
confidence: 99%
“…One important finding, which has influenced the hypotheses for this thesis, is that the myometrium is a lactate producer (Taggart & Wray 1993;Taggart et al 1996;Taggart et al 1997;Taggart & Wray 1998;Wray et al 2003;Quenby et al 2004), and the level will increase when there is a lack of oxygen.…”
Section: Introductionmentioning
confidence: 99%